Efektifitas Pelatihan Kesehatan Mental untuk Meningkatkan Kesejahteraan Psikologis Guru di SMP Inklusi - Rahma, Ulifa; Dara, Yuliezar Perwira; Kamaliya, Naila (Universitas Negeri Jakarta, 2026)
Inclusive education in Indonesia requires teachers to be prepared not only in pedagogical aspects but also in mental and psychological readiness to manage student diversity. However, many teachers still face challenges in terms of limited knowledge, skills, and psychological well-being in inclusive teaching practices. This community service program aimed to strengthen teachers’ mental readiness and psychological approaches through psychoeducational interventions. The program was conducted at SMP Negeri 10 Malang, involving 37 teachers, shadow teachers, and inclusive education teachers. The implementation method consisted of four psychoeducational sessions, including interactive lectures, case discussions, role play, and pretest–post-test-based evaluation. The analysis results showed a significant improvement in psychological well-being (M pretest = 81.9; M post-test = 90.3; p = 0.001). These findings indicate that the training successfully enhanced teachers’ mental readiness in facing the demands of inclusive education. Thus, psychoeducation is proven effective as a strategy to strengthen teachers’ capacity while providing practical implications for the development of sustainable training models based on psychological approaches. Keywords: inclusive education, teachers’ mental readiness, psychoeducation, psychological well-being, student diversity